2015
DOI: 10.5888/pcd12.150121
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Legislation to Improve Hospital Support of Breastfeeding, New York State, 2009–2013

Abstract: IntroductionIncreasing breastfeeding is a public health priority supported by strong evidence. In 2009, New York passed Public Health Law § 2505–a, requiring that hospitals support the World Health Organization’s (WHO’s) recommended “Ten Steps for Successful Breastfeeding” (Ten Steps). This legislation strengthened and codified existing New York State’s hospital perinatal regulations. The purpose of this study was to assess hospital policy compliance with New York laws and regulations related to breastfeeding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…1 Breastfeeding is beneficial to the child as it is natural with optimal nutrients and has several protective factors against infections. 2 Breastfeeding is eco-friendly and is advantageous to mother, as it reduces the time of bleeding during postnatal period and decreases the risk for malignancies, as well as to the community.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Breastfeeding is beneficial to the child as it is natural with optimal nutrients and has several protective factors against infections. 2 Breastfeeding is eco-friendly and is advantageous to mother, as it reduces the time of bleeding during postnatal period and decreases the risk for malignancies, as well as to the community.…”
Section: Introductionmentioning
confidence: 99%
“…2 Breastfeeding is eco-friendly and is advantageous to mother, as it reduces the time of bleeding during postnatal period and decreases the risk for malignancies, as well as to the community. 1 The National Family health Survey-3, in India, had revealed that only 46% of children are exclusively breastfed in the 0-1 month age group. 3 In India about 2.4 million children die each year of which two-thirds are associated with infant feeding practices which are inappropriate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The New York WIC program has a long history of promoting breastfeeding as a strategy to prevent childhood obesity †† . Moreover, New York and local governments enacted legislation ( 3 ) and the Latch-On §§ initiative to improve support of breastfeeding. The substantial progress in breastfeeding measures among New York WIC infants likely reflects the collective efforts at national, state and local levels.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to continue breastfeeding is influenced by a combination of demographic, socioeconomic, psychosocial, cultural, and environmental factors ( 3 , 6 8 ). The findings in this study indicate potential conceptual or methodological limitations in existing initiatives to promote duration and exclusivity.…”
Section: Discussionmentioning
confidence: 99%